Chronic myeloid leukaemia manifesting as a gynecological emergency in a young woman - Padmanabhan, Vishnupriya; Shahin, Mohamed M.; Abdallah, Karim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Chronic Myeloid Leukaemia (CML) is a form of blood cancer that is characterized by unregulated growth of Myeloid cells within the bone marrow. Idiopathic Spontaneous Intraperitoneal Haemorrhage (ISIH) is a rare life-threatening presentation. Case report of a young woman who presented to the emergency department with evidence of intra-abdominal bleeding. thought to be of gynaecological origin. No obvious source for the bleeding could be identified intra-operatively. Laboratory investigations showed evidence of Leukaemia which was confirmed on bone marrow biopsy. CML represents 8% of leukaemia in the UK. Despite being a rare presentation, ISIH should be considered as a possible differential diagnosis for those patients when presenting with evidence of acute abdomen.